Detection strategy targeting a chloramphenicol resistance gene from genetically modified bacteria in food and feed products. (February 2020) - Fraiture, Marie-Alice; Deckers, Marie; Papazova, Nina; Roosens, Nancy H.C.
Abstract: Genetically modified microorganisms (GMM), harbouring commonly antimicrobial resistance (AMR) genes as selection markers, are frequently used to produce food and feed enzymes, additives and flavourings. Such commercialized microbial fermentation products should not contain GMM, or associated recombinant DNA. Although the use of AMR genes gives rise to public health and environmental concerns regarding their potential acquisitions by pathogens and gut microbiota, no method targeting AMR genes harboured by such GMM is currently available for the enforcement laboratories. In reason of the increasing interest of the competent authorities to be able to assess the potential risks related to the presence of these AMR genes in microbial fermentation products, we propose therefore for the first time a PCR-based strategy easily implementable in enforcement laboratories. This strategy targets a chloramphenicol resistance gene, highlighted by the patent analysis performed in this study as being harboured by a noteworthy part of GMM producing microbial fermentation products from the food and feed industry. First, the potential presence of the AMR gene is detected by real-time PCR. Next, its full-length is evaluated by a nested-PCR amplifying a large fragment of its sequence to determine the risks of likely AMR gene acquisition. This strategy allows thus to support the competent authorities regarding the measures to be taken in case of unexpected DNA contaminations from such GMM in commercialized microbial fermentation products. Highlights: GMM harbouring AMR genes are often used in the food and feed industry. Due to health concerns linked to AMR genes, a control strategy is developed. A chloramphenicol resistance gene is targeted. After its detection, the full-length of the AMR gene is evaluated. Such results support the authorities to assess potential risks of AMR genes.